Pengaruh Daya Saing, Kurs, PDB, dan Harga Terhadap Ekspor Karet Alam Indonesia ke Lima Negara Tujuan Utama Tahun 2005–2020 - Michael Grabi Sinukaban; Ni Luh Karmini (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Natural rubber is a key export commodity in Indonesia, supporting the national economy alongside oil and gas. As the second-largest producer and exporter of rubber globally, Indonesia faces challenges in optimizing export value, particularly to major destination countries. Global demand for rubber, especially in the automotive and manufacturing sectors, is rising, creating significant opportunities for Indonesia. This study analyzes the impact of competitiveness, exchange rates, gross domestic product (GDP) of destination countries, and international prices on the value of Indonesian natural rubber exports to the United States, Japan, China, India, and South Korea from 2005 to 2020. Using an associative quantitative approach with panel data regression analysis, the study combines time series and cross-sectional data. Competitiveness is measured by the Revealed Comparative Advantage (RCA) method. The findings indicate that competitiveness, GDP of destination countries, and international prices positively and significantly affect export value. Higher competitiveness, GDP, and better international prices tend to increase export value. Conversely, exchange rates negatively affect export value, meaning that a depreciation of the rupiah can enhance exports by making rubber more competitive globally.